A biocompatible cross-linked fluorescent polymer prepared via ring-opening PEGylation of 4-arm PEG-amine, itaconic anhydride, and an AIE monomer1. Issue 19 (21st May 2015) - Ma, Chunping; Zhang, Xiqi; Wang, Ke; Zhang, Xiaoyong; Zhou, Yahong; Liu, Hongliang; Wei, Yen
<x xml:space="preserve">Abstract</x> A biocompatible cross-linked fluorescent polymer is prepared via ring-opening PEGylation of an AIE monomer, itaconic anhydride, and 4-arm PEG-amine.